Aviation Contrail Cirrus and Radiative Forcing Over Europe During 6 Months of COVID‐19. Issue 8 (28th April 2021) - Schumann, U.; Bugliaro, L.; Dörnbrack, A.; Baumann, R.; Voigt, C.
Abstract: The COVID‐19 pandemic led to a 72% reduction of air traffic over Europe in March–August 2020 compared to 2019. Modeled contrail cover declined similarly, and computed mean instantaneous radiative contrail forcing dropped regionally by up to 0.7 W m −2 . Here, model predictions of cirrus optical thickness and the top‐of‐atmosphere outgoing longwave and reflected shortwave irradiances are tested by comparison to Meteosat‐SEVIRI‐derived data. The agreement between observations and modeled data is slightly better when modeled contrail cirrus contributions are included. The spatial distributions and diurnal cycles of the differences in these data between 2019 and 2020 are partially caused by differences in atmospheric and surface conditions, particularly for solar radiation in the spring of 2020. Aviation signals become discernible in the observed differences of these data between 2019 and 2020 when subtracting numerical weather prediction model results that approximate the atmosphere and surface conditions without contrails. Plain Language Summary: Aircraft flying in cold and humid air masses induce contrails which warm the Earth‐atmosphere system by reducing the terrestrial radiation out into space and cool by increasing the Earth's albedo. Previous studies found that the warming effects dominate and that contrails may contribute most of the present radiative forcing of climate change induced by aviation. The COVID‐19 pandemic led to a worldwide and long‐duration reduction of air traffic. This paper compares model predictions and satellite‐observed cirrus properties and irradiances over Europe for 6 months in 2019 and 2020. The models account for changes in the atmosphere and at the Earth's surface in the two half‐years. Model and observation results show about 90% correlation and 20% mean normalized deviations. The agreement between observed and modeled optical cirrus thickness and terrestrial irradiances improves slightly when the modeled contrail cirrus contributions are included. Solar radiation changes show a larger variability because of large changes in the lower atmosphere and at the Earth surface. Since worldwide traffic activity has stayed at low levels after August 2020, the comparisons may be extended. Further model studies, including the effects of other emissions, are needed for a more comprehensive understanding of the observed changes. Key Points: Air traffic reduction during the COVID‐19 pandemic is used for testing aviation contrail cirrus and related radiative forcing modeling Cirrus optical depth and top‐of‐atmosphere irradiances from satellite observations and model results show reasonable correlations Aviation contrail signatures are identifiable in spite of strongly different atmosphere and surface conditions in 2019 and 2020